Foldable interpenetrated metal-organic frameworks/carbon nanotubes thin film for lithium–sulfur batteries - Yiyin Mao (Nature Portfolio, 2017)
Lithium sulfur batteries show capacity and cost advantages, but suffer from the insulating sulfur, shuttling effect and volume fluctuation. To address these challenges, the authors synthesize foldable composite electrodes with carbon nanotubes interpenetrating metal-organic frameworks.